1, 3‐Dioxolane: A Strategy to Improve Electrode Interfaces in Lithium Ion and Lithium‐Sulfur Batteries. Issue 9 (27th February 2018) - La Monaca, Andrea; De Giorgio, Francesca; Soavi, Francesca; Tarquini, Gabriele; Di Carli, Mariasole; Paolo Prosini, Pier; Arbizzani, Catia
Abstract: Batteries with increased specific energy will play a crucial role in future electrical energy. Indeed, high specific energy means increased driving ranges in electric vehicles and can also improve the efficient use of the renewable energy. Lithium batteries, including lithium ion batteries (LIBs), with a high specific energy can be achieved with the use of high‐potential and/or high specific capacity cathodes. We exploit the ability of 1, 3‐dioxolane (DOL) to polymerize at voltages higher than 4 V to produce a protective polymer layer in situ on two different cathodes. Specifically, DOL was polymerized on high‐voltage LiNi0.5 Mn1.5 O4 (LNMO) and on high‐capacity sulfur electrodes in order to reduce the electrode/electrolyte interface reactivity of these cathode materials and to improve cycling performance. Abstract : Battery iDOL : 1, 3‐Dioxolane (DOL) is electropolymerized in situ to produce a protective polyether‐based layer on two different cathodes, that is, high‐voltage LiNi0.5 Mn1.5 O4 (LNMO) for lithium ion batteries and high‐capacity sulfur electrodes for Li‐S batteries. The polyDOL layer is beneficial in enhancing the cycling stability of both cathodes by improving the LNMO/electrolyte interface and by minimizing polysulfide migration across the separator.